(untitled) (Mason, Ohio, 2007)
integrating relevant aspects of urban and financial economics. It bridges the gap between mainstream finance and the current cutting edge of professional real estate practice with a look at asset market inefficiency and illiquidity, after-tax analysis for various types of investors, tax-exempt institutions, and private investment. Other chapter topics include periodic returns measurement, risk analysis, asset valuation, investment analysis, leverage, capital structure, portfolio theory, and option valuation theory. For individuals aware of the importance of real estate, and interested in its financial economic aspects
Keywords: Commercial real estate,Real estate investment,Mortgages,Real property and taxation,Land use, Urban,Đầu tư địa ốc,Thuế sử dụng đất